(untitled) (Journal of Physical Education (Maringá), 2020)
Motor competence (MC) is an attribute associated with positive health behaviors; contextual factors, seems to play a important role for MC of children. The purpose of this study was to compare the MC of preschool children in two different years and to identify the effect of contextual factors (school type and family income). Two representative samples of children (3 to 5 years old) from Recife were assessed in two time periods: 2010 (n= 282 children, 151 boys) and 2012 (n=270 children, 148 boys). MC was assessed using the Test of Gross Motor Development - 2. Data analysis used the Anova Two-Way and the Ancova tests adjusted by type of school (public and private) and family income, a p <0.05 was used. Locomotor skills, object control and overall motor quotient were superior for the children analyzed in 2010. Furthermore, the school type and income increased the effect size in the differences in object control skills and the general motor quotient. We can conclude that there was a decrease in MC of the preschool population after two years and that the contextual variables type of school and family income are important for the development of MC.